Revolutionizing Oil and Gas Industries with Artificial Intelligence Technology - Musa, Abdulhamid (International Journal of Computer Sciences and Engineering, 2023)
The oil and gas industries must adapt and modernize their processes to stay competitive, reduce environmental impact, and promote sustainability. This involves investing in artificial intelligence, automation, and data analytics to streamline operations, improve efficiency, and reduce costs. The focus of this paper is the revolutionary impact of Artificial Intelligence technology on the oil and gas industries. However, the technology of Artificial Intelligence has revolutionized the oil and gas industries by automating processes like drilling and production, improving equipment reliability and safety, and providing valuable insights into reservoir management and supply chain management. Besides, there are risks and constraints, such as limited model generalizability and the need for new resources to train new datasets. Thus, using artificial intelligence in engineering can reduce costs and improve quality, but ethical considerations must be taken into account such as job displacement and ensuring the decisions by the artificial intelligence technology align with societal values. Integration of artificial intelligence requires careful examination of technical and ethical factors too. Accordingly, this study also highlights the immense potential of artificial intelligence in the oil and gas industry, while also acknowledging the need for careful consideration and implementation. By leveraging the power of artificial intelligence, we can unlock new discoveries and streamline processes in this vital industry.